PENGARUH KUALITAS PELAYAN DAN LOKASI TERHADAP LOYALITAS PELANGGAN PADA THE LAUNDRYS DI KOTA TANGERANG - Wildaniyah Hasanah; Novia Susanti (Journal of Research and Publication Innovation, 2024)
This study aims to determine the impact of service quality and location on customer loyalty at The Laundrys in Tangerang. The research method used is quantitative. The population of the study consists of 2,572 individuals. The sample used includes 96 respondents, obtained using Slovin's formula. Data collection was conducted using quantitative methods. The analysis methods used in this study include validity testing, reliability testing, normality testing, classical assumption testing, simple and multiple linear regression analysis, correlation coefficient testing, coefficient of determination testing, t-tests, and F-tests, with the aid of Statistical Package for Social Science (SPSS) for Windows version 27. The results of the study show that, partially, service quality has a positive and significant effect on customer loyalty with a t-value of 4,531> t-table value of 1.986 and a significance value of 0.000 < 0.05. Location also has a positive and significant effect on customer loyalty with a t-value of 9.433 > t-table value of 1.986 and a significance value of 0.000 < 0.05. Simultaneously, both service quality and location have a positive and significant effect on customer loyalty with an F-value of 115.925 > F-table value of 3,09 and a significance level of 0.000 < 0.05.